Prediction of network public opinion based on bald eagle algorithm optimized radial basis function neural network. Issue 2 (4th November 2021) - Xie, Jialiang; Zhang, Shanli; Lin, Ling
Abstract : Purpose: In the new era of highly developed Internet information, the prediction of the development trend of network public opinion has a very important reference significance for monitoring and control of public opinion by relevant government departments. Design/methodology/approach: Aiming at the complex and nonlinear characteristics of the network public opinion, considering the accuracy and stability of the applicable model, a network public opinion prediction model based on the bald eagle algorithm optimized radial basis function neural network (BES-RBF) is proposed. Empirical research is conducted with Baidu indexes such as "COVID-19", "Winter Olympic Games", "The 100th Anniversary of the Founding of the Party" and "Aerospace" as samples of network public opinion. Findings: The experimental results show that the model proposed in this paper can better describe the development trend of different network public opinion information, has good stability in predictive performance and can provide a good decision-making reference for government public opinion control departments. Originality/value: A method for optimizing the central value, weight, width and other parameters of the radial basis function neural network with the bald eagle algorithm is given, and it is applied to network public opinion trend prediction. The example verifies that the prediction algorithm has higher accuracy and better stability.